Virulence of Salmonella enteritidis phagetypes 4, 8 and 13 and other Salmonella spp. for day-old chicks, hens and mice. - Poppe, C (1993)
Virulence of three Canadian poultry strains of Salmonella enteritidis, namely phagetypes (PT) 4, 8 and 13, and one Salmonella heidelberg strain was assessed in orally and intraperitoneally inoculated one-day old chickens and compared to the virulence of a human S. enteritidis PT 4 strain from the United Kingdom (UK). The two PT 4 strains were also compared in orally inoculated adult laying hens. In addition, orally inoculated Balb/c mice were used to evaluate virulence of the above strains and two strains of Salmonella typhimurium containing different plasmids. In orally inoculated one-day old chickens, the UK S. enteritidis PT 4 strain was more virulent than the Canadian PT 4 strain. The UK PT 4 strain was also more virulent and invasive in adult laying hens than the Canadian PT 4 strain. The S. enteritidis PT 8 strain and one S. typhimurium strain isolated from a chicken hatchery were the most virulent for orally inoculated Balb/c mice. This strain of S. typhimurium contained the 60 megadalton plasmid associated with virulence for Balb/c mice which was not present in the S. typhimurium strain isolated from a pig with septicemic disease.